Common fuzzy hybrid fixed point theorems for a sequence of fuzzy mappings - Shi Chuan (International Journal of Mathematics and Mathematical Sciences)
In this paper, we discuss the concepts of fuzzy hybrid fixed points, of g-Φ-contractive type fuzzy mappings and common fuzzy hybrid fixed point theorems of a sequence of fuzzy mappings. Our theorems improve and generalize the corresponding recent important results.